Factors associated with severe respiratory syncytial virus disease in hospitalised children: a retrospective analysis. Issue 4 (15th September 2021) - Anderson, Jeremy; Oeum, Michelle; Verkolf, Eva; Licciardi, Paul V; Mulholland, Kim; Nguyen, Cattram; Chow, Kim; Waller, Gregory; Costa, Anna-Maria; Daley, Andrew; Crawford, Nigel W; Babl, Franz E; et al.
Abstract : Background: Early recognition of children at risk of severe respiratory syncytial virus (RSV) lower respiratory tract infection is important as it informs management decisions. We aimed to evaluate factors associated with severe disease among young children hospitalised with RSV infection. Methods: We conducted a retrospective cohort study of all children <2 years of age hospitalised for RSV lower respiratory tract infection at a single tertiary paediatric hospital over three RSV seasons (January 2017–December 2019). We classified children as having 'moderate' or 'severe' disease based on the level of respiratory intervention and used univariable and multivariable regression models to determine factors associated with severe disease. Results: Of 970 hospitalised children, 386 (40%) were classified as having 'severe' and 584 (60%) as having 'moderate' RSV disease. On multivariable analyses, age <2 months (OR: 2.3, 95% CI 1.6 to 3.3, p<0.0001), prematurity (OR: 1.6, 95% CI 1.1 to 2.4, p=0.02) and RSV–parainfluenza virus type 3 (PIV3) codetection (OR: 2.6, 95% CI 1.05 to 6.5, p=0.04) were independently associated with severe disease. Conclusion: Younger age, prematurity and PIV3 codetection were associated with severe RSV disease in children <2 years of age hospitalised with RSV infection. The association between PIV3 and severe RSV disease is a novel finding and warrants further investigation. Abstract : Respiratory syncytial virus (RSV) disease places a large burden on healthcare systems. Early recognition of children at risk of severe RSV disease may be useful. This study finds younger age (<2 months) and prematurity are associated with increased severity of RSV disease. An association between Para-influenza virus type 3/RSV co-detection and severe disease may warrant further investigation.